IMPLEMENTASI LAYANAN POSYANDU REMAJA BERBASIS TEKNOLOGI DI PULAU KASU KECAMATAN BELAKANG PADANG KOTA BATAM - Purba, Netty Herawaty; Fariningsih, Erika; Safitri, Murniati (Awal Bros Journal of Community Development, 2024)
Adolescent problems are complicated and require a thorough and integrated approach to be addressed. Adolescent Posyandu is associated with sex education, which seeks to acquire precise information. Furthermore, sex education is associated with comprehension, knowledge, and information. The number of regencies/cities that provide health services to people of reproductive age was achieved with the achievement of 4 regencies/cities from the target of 2 regencies/cities, according to the 2021 Government Agency Performance Accountability Report (LAKIP) for Public Health, Riau Islands Provincial Health Office. Aims to educate about health issues related to the use of technology in adolescent Posyandu services on Kasu Island. This approach to community involvement is used both offline and directly. Additionally, a questionnaire was administered before and after the activity to gauge the adolescents' understanding of counseling in relation to the use of technology-based adolescent poseyandu with adolescent mental health. 22 teenage girls who had menstruated between the ages of 11 and 23 made up the majority of respondents to the community service activities (pengabmas) on counseling related to the implementation of technology-based adolescent Posyandu with adolescent mental health. Thirteen of the respondents, or 59% of the total, had completed high school. Pre-test results revealed that most teenage girls had little understanding about the application of technology-based adolescent Posyandu with adolescent mental health, with as many as 22 persons (90%) having low knowledge. and the post-test revealed that the majority of participants up to 14 (63.6%) had a strong level of understanding following counseling through presentations.